Spontaneous Bacterial Coronary Sinus Septic Thrombophlebitis Treated Successfully Medically. Issue 3 (6th November 2013) - Fournet, Maxime; Behaghel, Albin; Pavy, Carine; Flecher, Erwan; Thebault, Christophe
Mini‐Abstract A 38‐year‐old farmer was hospitalized for fever, chills, cough, and chest pain lasting for 7 days. Due to persistent symptoms, patient was referred to hospital. Blood cultures identified oxacillin‐sensitive Staphylococcus aureus (OSSA). Transthoracic echocardiography (TTE) showed large pericardial effusion, a mobile heterogeneous mass originating from the coronary sinus ostium, no sign of valvular endocarditis. Pericardiocentesis was done carrying out purulent fluid, microbiological culture isolating an OSSA. Parenteral penicillin M was administered for 6 weeks. At the end of this antibiotherapy regimen, TTE showed no coronary sinus mass with complete vacuity of the coronary sinus vein and no pericardial effusion.